How POD can help you - Brotherston, S (Bodleian Libraries, University of Oxford, 2022)
The University's People and Organisational Development (POD) Team provide learning, professional development and organisational development support for staff and departments across the organisation. They have recently established a Professional Services hub and this is your opportunity to find out what support and opportunities might be available to you through that hub and the wider POD team.